COMPARISON OF EARLY NEEDLE-KNIFE SPHINCTEROTOMY VS STANDARD BILIARY CANNULATION IN PREVENTING ERCP ASSOCIATED PANCREATITIS IN CASES OF DIFFICULT BILIARY CANNULATION -A TERTIARY CARE EXPERIENCE - Muhammad Bilal Khattak,; Ehtisham Haider,; Muhammad Hafeez,; Khawar Shabir,; Rafiudin,; Khan, Hafizullah (Journal of Ayub Medical College Abbottabad, 2024)
Background: Post-ERCP pancreatitis (PEP) has been shown to increase by difficult biliary cannulation during ERCP. Increasingly used as an alternative to standard biliary cannulation to prevent this complication in difficult access cases is early needle-knife sphincterotomy (NKS). Objectives were to evaluate the efficacy of early needle knife sphincterotomy vs standard biliary cannulation in preventing post-ERCP pancreatitis in patients who have difficult biliary cannulation. This retrospective study was conducted at the Department of Gastroenterology and Hepatology, Pak Emirates Military Hospital from January to December 2022. Methods: Hundred patients who have difficult biliary cannulation in their ERCP were included. Patients were randomized, based on the attending endoscopist, to early NKS or standard biliary cannulation methods. The rate of PEP, procedure time and cannulation success rates were compared between the two groups. Results: It involved 100 patients with an average age of 50.3 years (±13.5) PEP occurred in 8% of the NKS group vs. 15% in the standard group (p=0.04). NKS group: significantly less time in procedure (mean 30 minutes) than the standard group (mean 45 minutes) (p=0.01). Conclusion: Early needle knife sphincterotomy, decreases risk of post-ERCP pancreatitis and procedure time compared to standard biliary cannulation. Thus, NKS represents a novel technique for early salvage of difficult cannulations.